Elevated first trimester C-reactive protein as a predictor of gestational diabetes - Parihar, Sanjay; Singh, Rajesh (International Journal of Advances in Medicine, 2019)
Background: The incidence of type 2 diabetes is increasing at an alarming rate, particularly among young women. GDM is a unique prediabetes state that shares common risk factors with type 2 diabetes, and similar alterations in carbohydrate metabolism. Objectives of this study the elevation of C-reactive protein in the first trimester of pregnancy as a predictor of gestational diabetes. Methods: This hospital-based study comprised of patients (Primigravida) visiting the obstetric OPD or admitted in Obstetric wards. Detailed history and clinical examination of the patient was recorded on a Proforma. Blood samples of patients were taken for: (i) C-reactive protein in first trimester of pregnancy; and (ii) Blood sugar (fasting & post-prandial) during their first antenatal visit and patients were followed up in subsequent visits in second and third trimester for development of gestational diabetes. Results: There were seven women who developed gestational diabetes and had elevated first trimester C- reactive protein levels as compared to other group in which only two women developed gestational diabetes mellitus but did not have elevated C-reactive protein in their first trimester. However, there were two women, who had elevated C-reactive protein, but did not subsequently develop gestational diabetes mellitus and women with C-reactive protein in normal range who did not develop gestational diabetes mellitus were 56. Conclusion: An association between first trimester inflammation marked by increased CRP levels, and subsequent risk of development of GDM has been identified.